Joint Impact Assessment of CTA's support to ANAFE (2003-2013) - Chakeredza, Sebastian; Yaye, Aissetou; Kaabunga, Enid (Technical Centre for Agricultural and Rural Cooperation, 2020)
The African Network for Agriculture, Agroforestry and Natural Resources Education (ANAFE) as a key partner of the Technical Centre for Agricultural and Rural Cooperation (CTA) was involved in the joint Capacity-centred Impact Pathway (CcIPA) study initiated in October 2012.